Uniaxial compression mechanical properties and fracture characteristics of brucite fiber reinforced cement-based composites. (15th March 2019) - Yang, Yuanyi; Deng, Yi; Li, Xingkui
Abstract: In this work, the mechanical properties, stress-strain behaviors, and microstructure of brucite fiber reinforced cement-based composites are determined. The results reveal that the incorporation of brucite fiber limits the compressive strength reinforcement of cement-based composite but leads to a significant increase of tensile strength by 136% and flexural strength by 73%. The employment of brucite fiber increases the fracture toughness K I c S and K I c Q of the cement-based composite by 450% and 98%. The incorporation of brucite fiber increases the linear elastic fracture toughness energy GF by 455% and elastic-plastic fracture toughness energy JC by 279%. The constitutive model of brucite fiber reinforced cement paste is also established. The diameter of the brucite fiber bundle is 1.5–16.3 μm, and the diameter of the single dispersed fiber is around 45–110 nm. There are about 15–363 single fibers in a bundle. Due to the brucite fiber possesses an intrinsic fibrous anisotropy, and network topology, the brucite fiber reinforced cement composites exhibit advantages of greater bending strength and crack bridging, as well as better crack resistance properties.